MTQ (Quizlet Modification Technology) in training Students’ Speaking Skills - Andri Kurniawan; Sharizan Sharizan; Yasvialan Arianta; Yenita Roza (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Sustainable Development Goals (SDGs) is a program to face the global issues set by the United Nations of General Assembly in 2015. Education is one the aspects related to the first pillar – human development. Some data about the quality of Indonesian education show that Indonesia is still facing many problems. The objectives of this paper are to describe the concepts and strategies of MTQ (Quizlet Modified Technology), in order to train critical thinking skills in English learning especially speaking skills and to describe the way of MTQ implementation in order to train critical thinking skills in English learning. The stage of discovery of the idea is done by observing the factual issues in the field of Indonesian education quality, especially in English subjects. Quizlet is one of the applications that people always use in learning English especially in improving their vocabulary. But, we can modify Quizlet becomes an application to use in training students’ speaking skills